RANCANG BANGUN SISTEM REM MOBIL LISTRIK FUSENA - Fauzan Ilham Maulana; Noorsakti Wahyudi; Indah Puspitasari (Jurnal Poli-Teknologi, 2019)
The brake system is a device to slow down or stop the movement of the wheel automatically so that the vehicle will move slowly. This completeness in the vehicle is very important and vital because it functions as a safety for life in driving. In the process of making the Electric Car Fusena brake system has steps in the process, consists of size planning, materials used, designs realized, manufacturing brake system supporting components, assembly, installation and testing of brake systems. The Fusena Electric Car brake system use a disc-type hydraulic brake system with one brake master that can work simultaneous with dual circuit fluids (front and rear braking). The comparison of the brake pedal is changed to 3: 1, designing and recreating the caliper stand to make it more precise so that it gets maximum brake performance and is better than the system used before. Static testing of the Fusena Electric Car hydraulic brake system is done by positioning the vehicle on an inclined plane at a slope of 15 and 20 with a variable driver load of 40 kg, 50 kg, 60 kg and 70 kg. The test results are that the vehicle does not experience displacement or movement. And the results of the average dynamic test of the Brake System at a speed of 27.3 km/h with an average braking distance of 171 cm = 1.71 meters and the average deceleration time is 0.26 seconds.